Pendekatan Strategis Manufacturing Terpadu Dalam Industri dan TQM - Farah Chalida Hanoum; Ria Kusumaningrum (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
The term integrated manufacturing is currently vogue and yet because of its poor definitation it is a concept which is difficult to apply. A strategic levell view of integrated manufacturing can provide a framework and some tools will be useful to the operating manager in thinking about integration. Meanwhile another way explaining the TQM revolution is to say that it focusses attention once new sense of time and relationship. Doing job right the first time requires investing resources in understanding system and enabling people to improve processes continually. TQM asks to focus an increasing quality of what is produced. The result of this different sense of time is usually a larger qualy and better quality. The new same of time goes hand in hand wuth a rethinking most important in organizations first and fore most, the relationship with employees must be rethought. Employees, according to TQM want responsibility, want to learn and improve and to demonstrate self-mastery and achievement. This is a far cry from treating employees as than who need to be helped and motivated to produce quality goods and services.